Effects of Freezing Ball Mill Treatment on the Structure and Physicochemical Properties of Oat Starch - Zhongyun ZHAO; Hui XU; Zongjun WU; Shengjun HAN; Zongwei HAO; Yiqun DU; Yaqing XIAO; Yingnan LIU; Kang LIU; Yongquan WANG; Shiyi LI; Mingming ZHENG; et al. (Shipin gongye ke-ji)
To investigate the effect of freezing ball milling on the structure and physicochemical properties of oat starch, the granule morphology, multiscale structure and physicochemical properties of oat starch were explored by ball milling at different ball milling time. The results showed that the polarization cross gradually disappeared and the starch granules disintegrated with the increase of ball milling time. The decrease in oat starch crystallinity and \begin{document}${R}_{\mathrm{1047/1022\;cm^{-1}}} $\end{document} ratio as well as the increase in the half-peak width at 480 cm−1 of the Raman spectrum indicated a decrease in long-range and short-range ordering, and the hydrogen bond structure within the starch was disrupted. The ΔH of oat starch was decreased from 8.73 J/g to 0.21 J/g and water absorption index increased significantly from 2.56 g/g to 5.69 g/g. Thermodynamic and hydration properties indicated a decrease in the thermal stability of oat starch. In addition, the setback, peak viscosity and storage modulus (G') of oat starch were reduced by ball milling. The above results indicated that freezing ball milling could be used as an effective physical process to modulate the structure of oat starch, this study was conducted with a view to provide a reference for the application of freezing ball milling process in oat starch processing.